AX composite zeolite and preparation method thereof

Through the step-by-step colloidal slurry treatment and incomplete crystallization method, the problem of incomplete reaction in the preparation of AX composite zeolite is solved, the utilization rate of effective components and product performance are improved, and the efficient preparation of AX composite zeolite is achieved.

CN119349594APending Publication Date: 2025-01-24ZHENGZHOU NON FERROUS METALS RES INST CO LTD OF CHALCO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411624801.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the existing preparation methods of AX composite zeolites, the incomplete reaction leads to problems such as high SiO2 residual amount in the crystallized mother liquor, narrow SiO2/Al2O3 ratio range, and low nonionic liquid carrying capacity (L.C.C).

Method used

By mixing the silicon source, first aluminum source, and alkali, the first glue paste is obtained, and incomplete crystallization is performed at the set temperature to generate the slurry containing X boilite, and then mixed with the second aluminum source The colloidal slurry is performed for the second time, and the slurry containing the AX composite zigza is generated, and the AX composite breaker was finally obtained through the solid liquid separation.

Benefits of technology

It improves the utilization rate of effective components in the AX composite zeolite reaction system, reduces the SiO2 residual amount, expands the SiO2/Al2O3 ratio range, and improves the non-ionic liquid carrying capacity (L.C.C) of the AX composite zeolite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349594A_ABST
    Figure CN119349594A_ABST
Patent Text Reader

Abstract

The invention relates to AX composite zeolite and a preparation method thereof, and belongs to the technical field of zeolite preparation. The method comprises the following steps: mixing and pulping a silicon source, a first aluminum source and alkali to obtain first colloid slurry; carrying out first incomplete crystallization on the first colloid slurry at a first set temperature to obtain slurry containing X zeolite; the slurry containing the X zeolite is mixed with a second aluminum source to obtain second colloidal slurry, and Na2O, Al2O3, SiO2 and H2O in chemical components of the second colloidal slurry meet the set molar ratio; and at a second set temperature, carrying out second incomplete crystallization on the second colloidal slurry to obtain the slurry containing the AX composite zeolite. The problems that in the prior art, the utilization rate of effective components of a reaction system of AX composite zeolite is low, the residual quantity of SiO2 in crystallization mother liquor is high, the range of SiO2 / Al2O3 of a product is narrow, and L.C.C is low are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of zeolite preparation, and in particular to an AX composite zeolite and a preparation method thereof. Background Art

[0002] At present, the well-known AX composite zeolite (or A-type and X-type mixed crystal zeolite, A / X composite zeolite, FAU / LTA co-crystallized zeolite, etc.) is mostly obtained by crystallization synthesis with one-time feeding in the same reaction system.

[0003] However, the synthesis method of AX composite zeolite by crystallization with one feed in the same reaction system has the problems of incomplete reaction, resulting in high residual content of effective components, especially SiO2 in the crystallization mother liquor, narrow range of product SiO2 / Al2O3 (molar ratio of SiO2 to Al2O3) and low LCC (non-ionic liquid carrying capacity). Summary of the invention

[0004] The present application provides an AX composite zeolite and a preparation method thereof to solve the following technical problem: how to improve the utilization rate of effective components in the reaction system of the AX composite zeolite.

[0005] In a first aspect, the present application provides a method for preparing an AX composite zeolite, comprising:

[0006] Mixing and slurrying a silicon source, a first aluminum source, and an alkali to obtain a first colloidal slurry;

[0007] At a first set temperature, subjecting the first colloidal slurry to a first incomplete crystallization to obtain a slurry containing X zeolite;

[0008] The slurry containing X zeolite is mixed with a second aluminum source to obtain a second colloidal slurry, wherein the chemical components of the second colloidal slurry include: Na2O, Al2O3, SiO2 and H2O; wherein the molar ratio of Na2O, Al2O3, SiO2 and H2O meets a set molar ratio;

[0009] At a second set temperature, the second colloidal slurry is subjected to a second incomplete crystallization to obtain a slurry containing AX composite zeolite.

[0010] Optionally, the first set temperature is 65°C to 80°C.

[0011] Optionally, the time for the first incomplete crystallization is 3 hours to 7 hours.

[0012] Optionally, the second set temperature is 65°C to 75°C.

[0013] Optionally, the time for the second incomplete crystallization is 2 hours to 4 hours.

[0014] Optionally, the X zeolite has a crystallinity of 25% to 70%.

[0015] Optionally, the set molar ratio of Na2O, Al2O3, SiO2 and H2O is (2.2-4.2):1:(1.95-2.05):(100-180).

[0016] Optionally, the chemical components of the first colloidal slurry include: Na2O, Al2O3, SiO2 and H2O; wherein,

[0017] The molar ratio of Na2O, Al2O3, SiO2 and H2O is (2.6~4.8):1:(2.5~3.4):(120~200).

[0018] Optionally, at the second set temperature, the second colloidal slurry is subjected to a second incomplete crystallization to obtain a slurry containing AX composite zeolite, and then the method further comprises:

[0019] The slurry containing AX composite zeolite is subjected to solid-liquid separation to obtain AX composite zeolite and mother liquor; wherein,

[0020] The AX composite zeolite meets the following indicators: LCC>80g / 100g-Z, the molar ratio of SiO2 to Al2O3 is 2.00-2.30;

[0021] The SiO2 concentration of the mother liquor is <1.0 g / L.

[0022] In a second aspect, the present application provides an AX composite zeolite, wherein the AX composite zeolite is prepared by the method described in any one of the embodiments of the first aspect.

[0023] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0024] The preparation method of the AX composite zeolite provided in an embodiment of the present application comprises: mixing and slurrying a silicon source, a first aluminum source and an alkali to obtain a first colloidal slurry; performing a first incomplete crystallization on the first colloidal slurry at a first set temperature to obtain a slurry containing X zeolite; mixing the slurry containing X zeolite with a second aluminum source to obtain a second colloidal slurry, wherein the chemical components of the second colloidal slurry include: Na2O, Al2O3, SiO2 and H2O; wherein the molar ratios of Na2O, Al2O3, SiO2 and H2O meet a set molar ratio; performing a second incomplete crystallization on the second colloidal slurry at a second set temperature to obtain a slurry containing AX composite zeolite. The silicon source, the first aluminum source and the alkali are mixed and slurried to produce a chemical reaction, thereby obtaining a first colloidal slurry; the first colloidal slurry is subjected to a first incomplete crystallization at a first set temperature, and the crystallinity of the X zeolite generated by the first incomplete crystallization can be regulated, thereby providing conditions for the subsequent generation of the AX composite zeolite; the slurry containing the X zeolite is mixed with the second aluminum source, and a chemical reaction can occur, thereby obtaining a second colloidal slurry, and the second aluminum source can consume the silicon source in the slurry containing the X zeolite, and serve as a raw material for generating the A zeolite; the chemical components of the second colloidal slurry include: Na2O, Al2O3, SiO2 and H2O, and the Na2O, Al2O3, SiO2 and H2O meet the set molar ratio, and the second colloidal slurry is subjected to a second incomplete crystallization at a second set temperature, so that the effective components of Al2O3 and SiO2 in the second colloidal slurry react completely, and the AX composite zeolite is fully generated, thereby improving the utilization rate of the effective components in the reaction system of the AX composite zeolite. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0027] Figure 1 A schematic diagram of a process for preparing an AX composite zeolite provided in an embodiment of the present application;

[0028] Figure 2 This is a SEM image of an AX composite zeolite provided in an embodiment of the present application;

[0029] Figure 3 This is an XRD diagram of an AX composite zeolite provided in an embodiment of the present application. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0031] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0032] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, the mass ratio of substance A, substance B, and substance C is 1:2:3, then substance A, substance B, and substance C should correspond one-to-one with the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.

[0033] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0034] At present, the synthesis method of AX composite zeolite by crystallization in the same reaction system at one time has the problem of incomplete reaction, resulting in high residual content of effective components, especially SiO2 in the crystallization mother liquor, narrow range of product SiO2 / Al2O3 ratio and low LCC (non-ionic liquid carrying capacity). The applicant discovered that the synthesis of X zeolite is obtained by crystallization in an excess silicon source system, that is, a synthesis system with a feed ratio of SiO2 / Al2O3=2.8 cannot obtain an X zeolite product with SiO2 / Al2O3=2.8, and can only synthesize an X zeolite with SiO2 / Al2O3<2.8 or even only SiO2 / Al2O3=2.3-2.4. At this time, the mother liquor still contains a part of SiO2, and the residual amount is 5-10g / L; while A zeolite can obtain a product with SiO2 / Al2O3=2.0 in a synthesis system with a feed ratio of SiO2 / Al2O3=1.95-2.05. The effective components Al2O3 and SiO2 in the mother liquor are almost consumed, and the residual amount is below 1.0g / L, which can be recycled as a dilute alkali solution recycle process ingredient. In view of the synthesis characteristics of X zeolite and A zeolite, in the first aspect, the present application provides a preparation method for AX composite zeolite, Figure 1 A schematic diagram of a process for preparing an AX composite zeolite provided in an embodiment of the present application; see Figure 1 ,include:

[0035] S1, mixing and slurrying a silicon source, a first aluminum source and an alkali to obtain a first colloidal slurry;

[0036] In some embodiments, the chemical components of the first colloidal slurry include: Na2O, Al2O3, SiO2 and H2O; wherein the molar ratio of Na2O, Al2O3, SiO2 and H2O is (2.6-4.8):1:(2.5-3.4):(120-200).

[0037] In the embodiment of the present application, the silicon source, the first aluminum source and the alkali are mixed and slurried to obtain a first colloidal slurry, which contains sodium aluminosilicate gel and can be used as a precursor for the subsequent first incomplete crystallization. The chemical composition of the first colloidal slurry satisfies: the molar ratio of Na2O, Al2O3, SiO2 and H2O can be (2.6-4.8):1:(2.5-3.4):(120-200), and according to this molar ratio, the X zeolite crystal phase synthesized by subsequent crystallization can be pure, avoiding the appearance of other impurities such as sodalite, P-type zeolite, etc., thereby ensuring the purity of the subsequent AX composite zeolite crystal phase and its various indicators. Exemplarily, in the chemical components of the first colloidal slurry, the molar ratio of Na2O, Al2O3, SiO2 and H2O may be 2.6:1:2.5:120, 4.8:1:3.4:200, 4.0:1:3.0:150, 3.5:1:3.2:180, 4.5:1:2.7:160, etc. In addition, the temperature of the reaction material in step S1 may be 35°C to 50°C.

[0038] A directing agent may be added to the first colloidal slurry, which can promote the nucleation process of the X zeolite on the one hand, and provide a directing effect to improve the crystallinity and purity of the X zeolite on the other hand; the volume of the directing agent may be ≤1% of the volume of the first colloidal slurry, and the molar ratio of the chemical components in the directing agent may satisfy: Na2O:Al2O3:SiO2:H2O=9:1:8:480.

[0039] S2, performing a first incomplete crystallization on the first colloidal slurry at a first set temperature to obtain a slurry containing X zeolite;

[0040] In some embodiments, the first set temperature is 65°C to 80°C.

[0041] In some embodiments, the X zeolite has a crystallinity of 25% to 70%.

[0042] In the embodiment of the present application, "the first set temperature" means the temperature of the first incomplete crystallization, and the first set temperature can be 65°C to 80°C, so that the crystallization of the X zeolite can be imperfect, that is, the X zeolite with a preset crystallinity can be obtained. If the first set temperature is higher than 80°C, the crystallinity of the X zeolite may be too high, and the crystal plane of the crystal of the X zeolite is too perfect, which may make it difficult to generate the AX composite zeolite in the future; or there is too little A zeolite in the AX composite zeolite, and the crystal morphology is more regular, which may reduce the LCC value of the AX composite zeolite product; if the first set temperature is lower than 65°C, the crystallinity of the X zeolite may be too low, and the subsequent addition of the second aluminum source may cause the crystallization to generate A zeolite, and ultimately the AX composite zeolite cannot be obtained. Exemplarily, the first set temperature can be 65°C, 67°C, 68°C, 69°C, 70°C, 72°C, 73°C, 74°C, 75°C, 76°C, 78°C, 79°C, 80°C, etc. The crystallinity of the X zeolite can be 25% to 70%, which can ensure the subsequent generation of the AX composite zeolite and improve the LCC value of the subsequent AX composite zeolite product. Exemplarily, the crystallinity of the X zeolite can be 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc.

[0043] In some embodiments, the time of the first incomplete crystallization is 3 hours to 7 hours.

[0044] In the embodiment of the present application, the first incomplete crystallization time can be 3h to 7h, and the crystallinity of the X zeolite is controlled in coordination with the temperature of the first incomplete crystallization. Exemplarily, the first incomplete crystallization time can be 3h, 4h, 5h, 6h, 7h, etc.

[0045] S3, mixing the slurry containing X zeolite with a second aluminum source to obtain a second colloidal slurry, wherein the chemical components of the second colloidal slurry include: Na2O, Al2O3, SiO2 and H2O; wherein the molar ratio of Na2O, Al2O3, SiO2 and H2O meets a set molar ratio;

[0046] In some embodiments, the set molar ratio of Na2O, Al2O3, SiO2 and H2O is (2.2-4.2):1:(1.95-2.05):(100-180).

[0047] In the embodiment of the present application, the set molar ratio of Na2O, Al2O3, SiO2 and H2O in the second colloidal slurry can be (2.2-4.2):1:(1.95-2.05):(100-180), so that the crystal phase of the generated AX composite zeolite is pure, the LCC value is high, and the effective components of Al2O3 and SiO2 in the second colloidal slurry react completely. Exemplarily, the molar ratio of Na2O, Al2O3, SiO2 and H2O in the second colloidal slurry can be 2.2:1:1.95:100, 4.2:1:2.05:180, 3.0:1:2.0:150, 3.5:1:2.03:160, 4.0:1:1.98:120, etc.

[0048] In addition, the silicon source can be a water glass solution, which satisfies the following indicators: SiO2 concentration can be 340g / L to 370g / L, and the modulus (molar ratio of SiO2 to Al2O3) is 3.0 to 3.2; the first aluminum source can be a sodium aluminate solution, which satisfies the following indicators: Al2O3 concentration can be 40g / L to 90g / L, and the caustic coefficient ak is 1.6 to 2.0; the alkali can be a sodium hydroxide aqueous solution, and the Na2O concentration of the sodium hydroxide aqueous solution can be 310g / L to 330g / L. The second aluminum source can be the same as the first aluminum source, or different, but the second aluminum source needs to meet the above-mentioned set molar ratio after being added.

[0049] S4. Performing a second incomplete crystallization on the second colloidal slurry at a second set temperature to obtain a slurry containing AX composite zeolite.

[0050] In some embodiments, the second set temperature is 65°C to 75°C.

[0051] In the embodiment of the present application, "the second set temperature" means the temperature of the second incomplete crystallization. The second set temperature can be 65°C to 75°C, which can make the effective components of Al2O3 and SiO2 in the second colloidal slurry react completely and the crystallinity of the generated AX composite zeolite be controlled to a certain extent. The crystallinity of the X zeolite in the AX composite zeolite can be 30% to 60%. If the second set temperature is higher than 75°C, the crystallinity of the AX composite zeolite may be too high, and the crystal plane of the crystal of the X zeolite is too perfect, thereby reducing the LCC value of the AX composite zeolite; if the second set temperature is lower than 65°C, the effective components of Al2O3 and SiO2 in the second colloidal slurry may not react completely or require a longer second crystallization time to complete the second crystallization process. Exemplarily, the second set temperature can be 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, etc.

[0052] In some embodiments, the second incomplete crystallization time is 2 hours to 4 hours.

[0053] In the embodiment of the present application, the second incomplete crystallization time can be 2h to 4h, and the temperature of the second incomplete crystallization is coordinated to make the effective components of Al2O3 and SiO2 in the second colloidal slurry react completely, and to achieve incomplete crystallization of the generated AX composite zeolite, so that the AX composite zeolite has a high LCC value. Exemplarily, the second incomplete crystallization time can be 2h, 2.5h, 3h, 3.5h, 4h, etc.

[0054] In some embodiments, the second colloidal slurry is subjected to a second incomplete crystallization at a second set temperature to obtain a slurry containing AX composite zeolite, and then further comprises:

[0055] The slurry containing AX composite zeolite is subjected to solid-liquid separation to obtain AX composite zeolite and mother liquor; wherein,

[0056] The AX composite zeolite meets the following indicators: LCC>80g / 100g-Z, the molar ratio of SiO2 to Al2O3 is 2.00-2.30;

[0057] The SiO2 concentration of the mother liquor is <1.0 g / L.

[0058] In an embodiment of the present application, a slurry containing AX composite zeolite is subjected to solid-liquid separation to obtain AX composite zeolite and a mother liquor. AX composite zeolite is a material composited by X zeolite and A zeolite. Both X zeolite and A zeolite belong to the zeolite family of minerals, and their crystal structure is mainly a three-dimensional network skeleton structure formed by silicon (Si) and aluminum (Al) connected by oxygen (O) bridges. The AX composite zeolite prepared in the present application meets the following indicators: LCC>80g / 100g-Z, the molar ratio of SiO2 to Al2O3 is 2.00-2.30, indicating that the AX composite zeolite has a pure crystal phase, a high LCC value, and the effective components of Al2O3 and SiO2 in the second colloidal slurry system react completely; the SiO2 concentration of the mother liquor is <1.0g / L, indicating that the SiO2 residue in the mother liquor is low. The above-mentioned AX composite zeolite can be washed with deionized water to a pH value of 9-10, and dried at a temperature of 70°C to 120°C to obtain an AX composite zeolite finished product. Exemplary, Figure 2 This is a SEM image of an AX composite zeolite provided in the examples of this application; see Figure 2 , indicating that zeolite A and zeolite X have no obvious grain boundaries and are zeolite AX composite, rather than a simple mixture of zeolite A and zeolite X. The surface of the crystal particles of the AX composite zeolite is very irregular, which makes the product have a very high LCC value. Figure 3This is an XRD diagram of an AX composite zeolite provided in the examples of the present application; see Figure 3 The XRD pattern shows the diffraction peaks of zeolite A and zeolite X, indicating that the AX composite zeolite was successfully prepared.

[0059] It should be noted that the LCC value refers to the non-ionic liquid carrying capacity of zeolite, and the "Zeolite Physical Property Determination Method Part 4: Determination of Non-ionic Liquid Carrying Capacity (LCC)" in the Nonferrous Metals Industry Standard of the People's Republic of China (YS / T 1065.4-2015). For LCC>80g / 100g-Z, where Z represents zeolite, LCC>80g / 100g-Z can be understood as 100g of zeolite can carry more than 80g of non-ionic liquid. Therefore, the AX composite zeolite prepared in the embodiment of the present application meets the requirements of the LCC index of the detergent additive for the super-concentrated powder detergent formula, and can be used as an additive for super-concentrated detergents, and can also be used as a deodorizing additive for rubber products.

[0060] In summary, the preparation method of AX composite zeolite provided in this application has the following advantages:

[0061] 1. Precise control of crystallinity: By setting specific temperatures for crystallization at different stages, the crystallinity of X zeolite can be precisely controlled, providing a guarantee for the synthesis of high-quality AX composite zeolite;

[0062] 2. Improve component utilization: Through reasonable step design, especially the second crystallization, the effective components are fully reacted, which reduces the waste of raw materials and improves the utilization efficiency of the effective components in the entire reaction system, which is conducive to reducing costs and improving product quality;

[0063] 3. Step-by-step synthesis to ensure product quality: The step-by-step synthesis method is used to first prepare X zeolite with specific properties, and then introduce new raw materials to synthesize AX composite zeolite. This method helps to better control the synthesis process and the final performance of the product;

[0064] 4. High LCC value of the product: A step-by-step synthesis method is adopted to control the temperature of the first incomplete crystallization, the temperature of the second incomplete crystallization and the chemical composition of the second colloidal slurry to regulate the crystallization degree of the AX zeolite crystals. The particle surface of the AX zeolite crystals is irregular and has a high LCC value.

[0065] In a second aspect, the present application provides an AX composite zeolite, wherein the AX composite zeolite is prepared by the method described in any one of the embodiments of the first aspect.

[0066] The AX composite zeolite is realized based on the preparation method of the above-mentioned AX composite zeolite. The specific steps of the preparation method of the AX composite zeolite can refer to the above-mentioned embodiment. Since the AX composite zeolite adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.

[0067] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for the unrecorded specific conditions in the following examples are usually measured according to national standards. If there is no corresponding national standard, then carry out according to general international standards, normal conditions or according to the conditions recommended by the manufacturer.

[0068] Example 1

[0069] A method for preparing AX composite zeolite, specifically comprising:

[0070] S11, mixing and slurrying a silicon source, a first aluminum source and an alkali to obtain a first colloidal slurry;

[0071] Specifically, deionized water, a silicon source (water glass solution) and a NaOH aqueous solution are sequentially added to a reaction tank, stirred for 10 minutes, and then a first aluminum source (sodium aluminate solution) is added, stirred for 40 minutes to obtain a first colloidal slurry; wherein the temperature of the materials added to the reaction tank is 46° C., and the chemical composition of the first colloidal slurry satisfies: Na2O:Al2O3:SiO2:H2O=4.8:1:3.2:180;

[0072] Adding a directing agent to the first colloidal slurry, wherein the volume of the directing agent is 0.1% of the volume of the first colloidal slurry;

[0073] S21, at a first set temperature, subjecting the first colloidal slurry to a first incomplete crystallization to obtain a slurry containing X zeolite; wherein the first set temperature is 65° C., the first incomplete crystallization time is 4.5 h, and the crystallinity of the X zeolite is 42%;

[0074] S31, mixing the slurry containing X zeolite with a second aluminum source (sodium aluminate solution) to obtain a second colloidal slurry, wherein the chemical components of the second colloidal slurry include: Na2O, Al2O3, SiO2 and H2O; wherein the molar ratio of Na2O, Al2O3, SiO2 and H2O satisfies a set molar ratio; the set molar ratio is Na2O:Al2O3:SiO2:H2O=4.2:1:1.97:140;

[0075] S41, performing a second incomplete crystallization on the second colloidal slurry at a second set temperature to obtain a slurry containing AX composite zeolite; wherein the second set temperature is 65° C. and the time for the second incomplete crystallization is 2.5 h;

[0076] S51. Perform solid-liquid separation on the slurry containing AX composite zeolite to obtain AX composite zeolite and mother liquor; wherein, the AX composite zeolite meets the following indicators: LCC=123g / 100g-Z, the molar ratio of SiO2 to Al2O3 is 2.02; the SiO2 concentration of the mother liquor is 0.29g / L.

[0077] Example 2

[0078] A method for preparing AX composite zeolite, specifically comprising:

[0079] S12, mixing and slurrying the silicon source, the first aluminum source and the alkali to obtain a first colloidal slurry;

[0080] Specifically, deionized water, a silicon source (water glass solution) and a NaOH aqueous solution are sequentially added to a reaction tank, stirred for 15 minutes, and then a first aluminum source (sodium aluminate solution) is added, stirred for 30 minutes, to obtain a first colloidal slurry; wherein the temperature of the materials added to the reaction tank is 44° C., and the chemical composition of the first colloidal slurry satisfies: Na2O:Al2O3:SiO2:H2O=3.8:1:3:200;

[0081] Adding a directing agent to the first colloidal slurry, wherein the volume of the directing agent is 0.3% of the volume of the first colloidal slurry;

[0082] S22, at a first set temperature, subjecting the first colloidal slurry to a first incomplete crystallization to obtain a slurry containing X zeolite; wherein the first set temperature is 80° C., the first incomplete crystallization time is 3 hours, and the crystallinity of the X zeolite is 60%;

[0083] S32, mixing the slurry containing X zeolite with a second aluminum source (sodium aluminate solution) to obtain a second colloidal slurry, wherein the chemical components of the second colloidal slurry include: Na2O, Al2O3, SiO2 and H2O; wherein the molar ratio of Na2O, Al2O3, SiO2 and H2O satisfies a set molar ratio; the set molar ratio is Na2O:Al2O3:SiO2:H2O=3.2:1:1.95:150;

[0084] S42, performing a second incomplete crystallization on the second colloidal slurry at a second set temperature to obtain a slurry containing AX composite zeolite; wherein the second set temperature is 70° C. and the time for the second incomplete crystallization is 2 hours;

[0085] S52, separating the slurry containing AX composite zeolite into solid and liquid to obtain AX composite zeolite and mother liquor; wherein, the AX composite zeolite meets the following indicators: LCC=81g / 100g-Z, the molar ratio of SiO2 to Al2O3 is 2.10; the SiO2 concentration of the mother liquor is 0.43g / L.

[0086] Example 3

[0087] A method for preparing AX composite zeolite, specifically comprising:

[0088] S13, mixing and slurrying the silicon source, the first aluminum source and the alkali to obtain a first colloidal slurry;

[0089] Specifically, deionized water, a silicon source (water glass solution), and a NaOH aqueous solution are sequentially added to a reaction tank, stirred for 20 minutes, and then a first aluminum source (sodium aluminate solution) is added, stirred for 50 minutes, to obtain a first colloidal slurry; wherein the temperature of the materials added to the reaction tank is 50° C., and the chemical composition of the first colloidal slurry satisfies: Na2O:Al2O3:SiO2:H2O=3.6:1:2.8:140;

[0090] Adding a directing agent to the first colloidal slurry, wherein the volume of the directing agent is 1% of the volume of the first colloidal slurry;

[0091] S23, at a first set temperature, subjecting the first colloidal slurry to a first incomplete crystallization to obtain a slurry containing X zeolite; wherein the first set temperature is 75° C., the first incomplete crystallization time is 4 hours, and the crystallinity of the X zeolite is 70%;

[0092] S33, mixing the slurry containing X zeolite with a second aluminum source (sodium aluminate solution) to obtain a second colloidal slurry, wherein the chemical components of the second colloidal slurry include: Na2O, Al2O3, SiO2 and H2O; wherein the molar ratio of Na2O, Al2O3, SiO2 and H2O satisfies a set molar ratio; the set molar ratio is Na2O:Al2O3:SiO2:H2O=3.1:1:1.95:110;

[0093] S43, performing a second incomplete crystallization on the second colloidal slurry at a second set temperature to obtain a slurry containing AX composite zeolite; wherein the second set temperature is 68° C. and the time for the second incomplete crystallization is 3 hours;

[0094] S53, separating the slurry containing AX composite zeolite into solid and liquid to obtain AX composite zeolite and mother liquor; wherein, the AX composite zeolite meets the following indicators: LCC=93g / 100g-Z, the molar ratio of SiO2 to Al2O3 is 2.00; the concentration of SiO2 in the mother liquor is 0.75g / L.

[0095] Example 4

[0096] A method for preparing AX composite zeolite, specifically comprising:

[0097] S14, mixing and slurrying the silicon source, the first aluminum source and the alkali to obtain a first colloidal slurry;

[0098] Specifically, deionized water, silicon source (water glass solution), and NaOH aqueous solution are added to the reaction tank in sequence, stirred for 15 minutes, and then the first aluminum source (sodium aluminate solution) is added, stirred for 30 minutes, to obtain a first colloidal slurry; wherein the temperature of the materials added to the reaction tank is 38° C., and the chemical composition of the first colloidal slurry satisfies: Na2O:Al2O3:SiO2:H2O=2.6:1:2.7:120;

[0099] S24, at a first set temperature, subjecting the first colloidal slurry to a first incomplete crystallization to obtain a slurry containing X zeolite; wherein the first set temperature is 80° C., the first incomplete crystallization time is 5 hours, and the crystallinity of the X zeolite is 57%;

[0100] S34, mixing the slurry containing X zeolite with a second aluminum source (sodium aluminate solution) to obtain a second colloidal slurry, wherein the chemical components of the second colloidal slurry include: Na2O, Al2O3, SiO2 and H2O; wherein the molar ratio of Na2O, Al2O3, SiO2 and H2O satisfies a set molar ratio; the set molar ratio is Na2O:Al2O3:SiO2:H2O=2.2:1:2.0:100;

[0101] S44, performing a second incomplete crystallization on the second colloidal slurry at a second set temperature to obtain a slurry containing AX composite zeolite; wherein the second set temperature is 75° C. and the time for the second incomplete crystallization is 3 hours;

[0102] S54, performing solid-liquid separation on the slurry containing AX composite zeolite to obtain AX composite zeolite and mother liquor; wherein, the AX composite zeolite meets the following indicators: LCC=94g / 100g-Z, the molar ratio of SiO2 to Al2O3 is 2.15; the SiO2 concentration of the mother liquor is 0.8g / L.

[0103] Example 5

[0104] A method for preparing AX composite zeolite, specifically comprising:

[0105] S15, mixing and slurrying the silicon source, the first aluminum source and the alkali to obtain a first colloidal slurry;

[0106] Specifically, deionized water, silicon source (water glass solution), and NaOH aqueous solution are added to the reaction tank in sequence, stirred for 15 minutes, and then the first aluminum source (sodium aluminate solution) is added, stirred for 45 minutes, to obtain a first colloidal slurry; wherein the temperature of the materials added to the reaction tank is 35° C., and the chemical composition of the first colloidal slurry satisfies: Na2O:Al2O3:SiO2:H2O=3.8:1:3.4:170;

[0107] Adding a directing agent to the first colloidal slurry, wherein the volume of the directing agent is 0.5% of the volume of the first colloidal slurry;

[0108] S25, at a first set temperature, subjecting the first colloidal slurry to a first incomplete crystallization to obtain a slurry containing X zeolite; wherein the first set temperature is 75° C., the first incomplete crystallization time is 6 hours, and the crystallinity of the X zeolite is 65%;

[0109] S35, mixing the slurry containing X zeolite with a second aluminum source (sodium aluminate solution) to obtain a second colloidal slurry, wherein the chemical components of the second colloidal slurry include: Na2O, Al2O3, SiO2 and H2O; wherein the molar ratio of Na2O, Al2O3, SiO2 and H2O satisfies a set molar ratio; the set molar ratio is Na2O:Al2O3:SiO2:H2O=3.2:1:2.05:140;

[0110] S45, performing a second incomplete crystallization on the second colloidal slurry at a second set temperature to obtain a slurry containing AX composite zeolite; wherein the second set temperature is 68° C. and the time for the second incomplete crystallization is 3 hours;

[0111] S55. Perform solid-liquid separation on the slurry containing AX composite zeolite to obtain AX composite zeolite and mother liquor; wherein, the AX composite zeolite meets the following indicators: LCC=120g / 100g-Z, the molar ratio of SiO2 to Al2O3 is 2.26; the SiO2 concentration of the mother liquor is 0.6g / L.

[0112] Comparative Example 1

[0113] Based on the disclosure of Example 1, the preparation method of an AX composite zeolite provided in Comparative Example 1 is different from that in Example 1 in that: the first set temperature is 85°C.

[0114] AX composite zeolite meets the following indicators: LCC=68g / 100-Z, the molar ratio of SiO2 to Al2O3 is 2.15; the concentration of SiO2 in the mother liquor is 0.6g / L.

[0115] Comparative Example 2

[0116] Based on the disclosure of Example 1, the preparation method of an AX composite zeolite provided in Comparative Example 2 is different from that in Example 1 in that: the second set temperature is 80°C.

[0117] AX composite zeolite meets the following indicators: LCC = 76g / 100g-Z, the molar ratio of SiO2 to Al2O3 is 2.02; the concentration of SiO2 in the mother liquor is 0.20g / L.

[0118] Comparative Example 3

[0119] Deionized water, water glass, and NaOH aqueous solution were added to the reaction tank in sequence, stirred for 30 minutes, and then sodium aluminate solution was added, stirred for 45 minutes to obtain a colloidal slurry; wherein the temperature of the materials added to the reaction tank was 40° C., and the chemical composition of the colloidal slurry satisfied: Na2O:Al2O3:SiO2:H2O=4.5:1:2.6:160;

[0120] Adding a directing agent to the colloidal slurry, wherein the volume of the directing agent is 0.5% of the volume of the colloidal slurry;

[0121] The colloidal slurry is aged at a temperature of 72° C. for 8 hours to obtain an aged slurry; the aged slurry is crystallized at a temperature of 95° C. for 4 hours to obtain a crystallized slurry; the crystallized slurry is solid-liquid separated, washed and dried to obtain an AX composite zeolite and a mother liquor.

[0122] AX composite zeolite meets the following indicators: LCC=72g / 100g-Z, the molar ratio of SiO2 to Al2O3 is 2.10; the concentration of SiO2 in the mother liquor is 10.4g / L.

[0123] From the analysis of the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 3, it can be seen that the preparation method of the AX composite zeolite provided in the examples of the present application, the prepared AX composite zeolite meets the following indicators: LCC>80g / 100g-Z, the molar ratio of SiO2 to Al2O3 is 2.00-2.30; the concentration of SiO2 in the mother liquor is <1.0g / L. The first set temperature (the first incomplete crystallization temperature) of Comparative Example 1 is too high, the second set temperature (the second incomplete crystallization temperature) of Comparative Example 2 is too high, and Comparative Example 3 adopts a one-step preparation of the AX composite zeolite, which to a certain extent makes the indicators of the prepared AX composite zeolite lower than those of the examples, especially the high residual amount of SiO2 in the separated mother liquor.

[0124] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:

[0125] (1) The preparation method of AX composite zeolite provided in the embodiment of the present application does not require high-temperature crystallization in the entire preparation process, saving energy consumption; the effective components Al2O3 and SiO2 in the final mother liquor are almost completely consumed, and the residual SiO2 is below 1.0g / L, which improves the utilization rate of the effective components of the reaction system and the product output rate. The mother liquor can be recycled as a dilute alkali solution back to the process ingredients, reducing production costs. The molar ratio of SiO2 to Al2O3 of AX composite zeolite is 2.00-2.30, which can meet the softening requirements of water with different hardness and different calcium ion / magnesium ion content;

[0126] (2) The preparation method of AX composite zeolite provided in the embodiment of the present application is a method for synthesizing AX composite zeolite by step-by-step feeding, that is, an aluminum source is added to the crystallization slurry of X zeolite again, so that the SiO2 remaining in the X zeolite mother liquor reacts with it to form AX composite zeolite. The process flow is simple, easy to operate, the utilization rate of reactants is high, and the cost is low;

[0127] (3) The preparation method of AX composite zeolite provided in the embodiment of the present application overcomes the problems of incomplete reaction of effective components of the reaction system of AX composite zeolite in the prior art, low utilization rate, high residual SiO2 in the crystallization mother liquor, narrow SiO2 / Al2O3 range of the product, and low LCC (non-ionic liquid carrying capacity);

[0128] (4) The AX composite zeolite provided in the embodiments of the present application has a wide range of SiO2 / Al2O3 ratios and a high LCC value, which can adapt to and meet the requirements of water hardness in different regions and detergent additives of different types of detergents.

[0129] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing AX composite zeolite, comprising: Mixing and slurrying a silicon source, a first aluminum source, and an alkali to obtain a first colloidal slurry; At a first set temperature, subjecting the first colloidal slurry to a first incomplete crystallization to obtain a slurry containing X zeolite; The slurry containing X zeolite is mixed with a second aluminum source to obtain a second colloidal slurry, wherein the chemical components of the second colloidal slurry include: Na2O, Al2O3, SiO2 and H2O; wherein the molar ratio of Na2O, Al2O3, SiO2 and H2O meets a set molar ratio; At a second set temperature, the second colloidal slurry is subjected to a second incomplete crystallization to obtain a slurry containing AX composite zeolite.

2. The method according to claim 1, characterized in that The first set temperature is 65°C to 80°C.

3. The method according to claim 1 or 2, characterized in that: The time of the first incomplete crystallization is 3 hours to 7 hours.

4. The method according to claim 1, characterized in that: The second set temperature is 65°C to 75°C.

5. The method according to claim 1 or 4, characterized in that: The second incomplete crystallization time is 2 hours to 4 hours.

6. The method according to claim 1, characterized in that The crystallinity of the X zeolite is 25% to 70%.

7. The method according to claim 1, characterized in that The set molar ratio of Na2O, Al2O3, SiO2 and H2O is (2.2~4.2):1:(1.95~2.05):(100~180).

8. The method according to claim 1, characterized in that The chemical components of the first colloidal slurry include: Na2O, Al2O3, SiO2 and H2O; wherein, The molar ratio of Na2O, Al2O3, SiO2 and H2O is (2.6~4.8):1:(2.5~3.4):(120~200).

9. The method according to claim 1, characterized in that: The second colloidal slurry is subjected to a second incomplete crystallization at the second set temperature to obtain a slurry containing AX composite zeolite, and then further comprises: The slurry containing AX composite zeolite is subjected to solid-liquid separation to obtain AX composite zeolite and mother liquor; wherein, The AX composite zeolite meets the following indicators: LCC>80g / 100g-Z, the molar ratio of SiO2 to Al2O3 is 2.00-2.30; The SiO2 concentration of the mother liquor is <1.0 g / L.

10. An AX composite zeolite, wherein the AX composite zeolite is prepared by the method according to any one of claims 1 to 9.